2020
DOI: 10.21203/rs.3.rs-34689/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Citations and publication rate of preprints on pharmacological interventions for COVID-19: The good, the bad and, the ugly.

Abstract: Background: Preprints are preliminary reports that have not been peer-reviewed. On December 2019, a novel coronavirus appeared in China, and since then, scientific production, including preprints, has drastically increased. In this study, we intend to evaluate how often preprints regarding pharmacological interventions against COVID-19 were cited, in spite of the fact that some of these preprints remained unpublished.Methods: We conducted a search on medRxiv and bioRxiv to identify preprints related to pharmac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Among these, almost half (11/23, 48%) had modifications in the title or results section, although the nature of these modifications is not described. 10 An analysis of spin in preprints and journal publications for COVID-19 trials found a single difference between two matched pairs of preprints and their journal publications: the discussion of limitations in the abstract. Limitations were discussed in the abstract of one article, but not in its accompanying preprint.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, almost half (11/23, 48%) had modifications in the title or results section, although the nature of these modifications is not described. 10 An analysis of spin in preprints and journal publications for COVID-19 trials found a single difference between two matched pairs of preprints and their journal publications: the discussion of limitations in the abstract. Limitations were discussed in the abstract of one article, but not in its accompanying preprint.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is reinforced by comparisons between preprints and publications on metrics like the basic reproduction number, transmissibility, incubation period, and infectious period, showing no evidence for a difference in the results presented in peer-reviewed vs. non-peer-reviewed literature (33,34). Nonetheless, a large portion of COVID-19 preprints show substantial changes in methods and results after peer-review (nearly half of the preprints analysed by Oikonomidi (2020) and Nicolalde et al (2020) (25,27)), suggesting flaws in the most essential elements of many COVID-19 preprints. At least two potential solutions for distinguishing high-from low-quality research in preprints are possible: 1) introducing quality control measures, and 2) educating the readership of preprints to make quality evaluations themselves.…”
Section: Constructing and Validating Precheck: A Checklist To Evaluat...mentioning
confidence: 98%
“…While it is true that many preprints never convert into publications (70-80% as of April 2021, see e.g., 25,26) and that unpublished preprints tend to be less cited than published ones (27,28), this is not necessarily due to poor quality. For one, the link between a preprint and its publication may be lost when it is the preprint that gets cited (29).…”
Section: Constructing and Validating Precheck: A Checklist To Evaluat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, almost half (11/23, 48%) had modifications in the title or results section, although the nature of these modifications is not described. [10] An analysis of spin in preprints and journal publications for COVID-19 trials found a single difference between 2 matched pairs preprint and their journal publications: the discussion of limitations in the abstract. Limitations were discussed in the abstract of one article, but not its accompanying preprint.…”
Section: Introductionmentioning
confidence: 99%